As trajetórias e características do Youtube e Globo Media Center/Globo Vídeos: um olhar comunicacional sobre as lógicas operativas de websites de vídeos para compreender a constituição do caráter midiático da web - Fischer, Gustavo Daudt (Universidade do Vale do Rio do Sinos, 2008)
The objective of this research is to understand how the web constitutes itself as a medium based on a proposition of a communicational approach and the exam of the most relevant proprieties of two paradigmactical cases of websites that present videos on their interfaces: Globo Media Center/Globo Vídeos, originated from a strong brazilian media group, whose importance is mostly related to their television presence (Organizações Globo) and YouTube, a website already originated in the web. In order to do this, we start by presenting issues regarding the relationship between the field of Communcation studies and the objects presented in the Internet, most likely the World Wide Web (web), pointing the moment that these websites appeared and indicating three sides that form our angle of observation: database, media and relationship environment. After these considerations, we move forward in order to place the role of video in media and understand the development of our chosen websites in time and present their prop
Keywords: comunicação; Globo Media Center; Globo Vídeos; interfaces; mídia; vídeo; YouTube; Web; communication; interfaces; medium; media; Ciências Sociais Aplicadas